GRADIENT ALIGNMENT MATERIALS WITH DIFFERENT PHOTOSENSITIVITY FOR TUNABLE POLARIZATION-INDEPENDENT LIQUID CRYSTAL LENS - V. S. Bezruchenko; A. A. Muravsky; A. A. Murauski; A. I. Stankevich; U. V. Mahilny (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The development of electrically tunable liquid crystal (LC) lenses is perspective and promising for a wide range of applications, for example, for imaging system, pico projectors, optical zoom systems, ophthalmology applications and other. Of particular note is the development of polarization-independent LC lenses, as eliminates polarizers from application devices that reduce the efficiency of light transmission through optical systems. Alignment benzaldehyde photosensitive materials, capable of changing the pretilt angles of nematic LC from 90 to 0 ºС in a controlled manner under UV exposure are developed. The anisotropy of the benzaldehyde alignment layers is generated by a two-stage treatment consisting of uniform rubbing with a cloth and subsequent non-polarized UV exposure. Inhomogeneous UV exposure of uniformly rubbed alignment layers allows formation of refractive index gradient inside the LC cell. The concept of tunable polarization-independent self-aligned LC lens based on gradient pretilt angle alignment materials with different photosensitivity is demonstrated. Self-alignment of two polarization-dependent sub-lens is achieved due to a single UV exposure act of two alignment layers, which are located on the same piece of glass on both sides, forming one common optical axis for a polarization-independent LC lens. The independence of the polarization of LC lenses is achieved by setting the azimuthal rubbing direction of the alignment layers of two polarizationdependent LC lenses perpendicular to each other. The sub-lens cells have uniform cell gap and are independently controlled using low-voltage driving. Devices based on gradient benzaldehyde alignment materials can be used in many modern optical and photonic devices.